At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
[tex]d = \sqrt{ (x_{1} - x_{2})^{2} + (y_{1} - y_{2})^{2} } \\ d = \sqrt{ (4 - (-2))^{2} + (-2 - 3)^{2} } \\ d = \sqrt{ (6)^{2} + (-5)^{2} } \\ d = \sqrt{ 36 + 25} \\ d = \sqrt{ 61 } \\ d = 7.81024... \\ d = 7.8[/tex]
Answer:
7.81
Step-by-step explanation:
Using the formula for finding the distance between two points as shown:
TU = √(y2-y1)²+(x2-x1)²
Given T = (4,-2) and U = (-2,3)
x1 =4, y1 = -2, x2 = -2, y2 = 3
Substituting this values into the formula, we have;
TU = √{3-(-2)}²+(-2-4)²
TU = √(3+2)²+(-2-4)²
TU = √5²+(-6)²
TU = √25+36
TU = √61
TU = 7.81
The distance between the two points is 7.81
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.